Fiscal and demographic drivers of public education spending in Malaysia (1971–2017): ARDL evidence - Yun, Wong Sing; Pinjaman, Saizal; Yassin, Jain; Zhang, RuiQi; Yuliadi, Imamudin (Asian Development Policy Review, 2026)
This study examines the fiscal factors influencing education expenditure in Malaysia, emphasizing the relationship between fiscal policies and demographic trends. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach, the analysis identifies both short-term and long-term relationships affecting public education funding. Results indicate that public debt and tax revenue significantly impact education spending, suggesting that government budget adjustments respond to fiscal conditions. Additionally, demographic factors, including population growth, play a substantial role in shaping budgetary decisions related to education. These findings enhance existing theoretical models by integrating fiscal and demographic variables into the analysis of public education expenditure. The research contributes valuable empirical evidence from a developing country context and offers practical policy recommendations. It highlights the importance of adopting more flexible and demographically aware fiscal strategies to sustain investment in education. The insights gained aim to guide future policymaking, particularly in improving the effectiveness and responsiveness of public education financing.